ECONOMIC RESTRUCTURING AND MIGRATION ASSIMILATION IN THE EU: THE ROLE OF DIVERSE ECONOMIC MODELS - Olha Yeremenko; Oleksandr Hrytsenko (Соціально-економічні відносини в цифровому суспільстві)
The European Union (EU) is made up of several economic systems, each affecting migration policies and integration processes uniquely. Though some economies value welfare protections and social stability, others focus on market liberalisation and labour flexibility. Especially in the context of post-crisis economic reorganization, this research examines the effects of mixed economic, social market, and neoliberal policies on migrant integration. The study uses qualitative comparative analysis to investigate information mainly from Eurostat and policy reports of 2007-2023. Classified into three economic models (neoliberal, social market, and mixed), the study evaluates how institutional support, social expenditure, and labour market structures help to define migrant inclusion among member states of the EU. The results point to major variations in migrant employment stability, access to social benefits, and possibilities for long-term integration across various economic systems. The outcomes imply that social market economies (e.g., Germany, Sweden, France) have the most complete support systems, therefore resulting in better long-term integration rates even in the face of initial labour market rigidities and significant financial costs. Quick access to work but at the expense of unstable employment and scant social protection characterizes neoliberal economies, which sometimes keep immigrants stuck in low-wage, unstable jobs (e.g., Estonia, Ireland, pre-Brexit UK). Mixed economies (e.g., Greece, Poland, Italy) suffer from erratic policies and financial limitations, hence high employment disparities and ongoing migratory poverty levels. The research emphasizes from a policy point of view the need for varied EU policies that match the structural facts of every economic model. One should consider the role of public debt in funding integration programs, strengthening welfare mechanisms in mixed economies, and incorporating migration metrics into national budget development. Given the changing demographics and economic currents in the EU, a flexible but coordinated strategy is vital to negotiate sustainable social inclusion with economic development.